2016
DOI: 10.15578/iaj.7.1.2012.1-10
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC VARIABILITY OF THREE POPULATIONS OF FLYING FISH, Hirundichthy oxycephalus FROM MAKASSAR STRAIT

Abstract: Flying fish, Hirundichthy oxycephalus is one of economically important marine species to Indonesia, particularly in Makassar Strait and Flores Sea. However, there is a limited published data on genetic variation in molecular marker level of this species. Random Amplified Polymorphic DNA (RAPD) was employed in this study to determine the genetic variability of three populations of flying fish collected from Takalar, Pare-Pare, and Majene in Makassar Strait. Genomic DNA was isolated from preserved muscle tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Parenrengi et al (2012) mengemukakan tiga fragmen dari primer CA-01 (700 bp, 800 bp, dan 1.000 bp) dan empat fragmen (225 bp, 400 bp, 750 bp, dan 850 bp) dari primer P-40 merupakan fragmen yang selalu ada pada setiap individu dari tiga populasi ikan terbang (Hirundichthy oxycephalus) dapat dianggap sebagai marka spesifik spesies. Pada penelitian menggunakan tiga spesies ikan kerapu (Epinephelus aerolatus, E. merra, dan E. suillus), Parenrengi (2006) berhasil mendeterminasi lima fragmen (OPA02-950 bp, OPA08-950 bp, OPA16-700 bp, OPA16-550 bp, OPA17-860 bp) dan terindikasi sebagai marka spesifik genus Epinephelus karena fragmen tersebut muncul pada tiga spesies ikan kerapu yang diuji.…”
Section: Keragaman Genetik Tiga Generasi Ikan Tambakan (Helostoma Temunclassified
“…Parenrengi et al (2012) mengemukakan tiga fragmen dari primer CA-01 (700 bp, 800 bp, dan 1.000 bp) dan empat fragmen (225 bp, 400 bp, 750 bp, dan 850 bp) dari primer P-40 merupakan fragmen yang selalu ada pada setiap individu dari tiga populasi ikan terbang (Hirundichthy oxycephalus) dapat dianggap sebagai marka spesifik spesies. Pada penelitian menggunakan tiga spesies ikan kerapu (Epinephelus aerolatus, E. merra, dan E. suillus), Parenrengi (2006) berhasil mendeterminasi lima fragmen (OPA02-950 bp, OPA08-950 bp, OPA16-700 bp, OPA16-550 bp, OPA17-860 bp) dan terindikasi sebagai marka spesifik genus Epinephelus karena fragmen tersebut muncul pada tiga spesies ikan kerapu yang diuji.…”
Section: Keragaman Genetik Tiga Generasi Ikan Tambakan (Helostoma Temunclassified
“…research on the genetic diversity of flying fish has been conducted in various locations worldwide; the first finding of flying fish Cypselurus opisthopus in southeastern waters of India (Jayakumar et al 2019), identification of flying fish DNA in Australian waters using cytochrome b found that the genus Cheilopogon is not monopiletic (Lewallen et al 2011(Lewallen et al , 2016Lewallen 2012;Gordeeva and Shakhovskoi 2017), identification of flying fish DNA down to the genus level has been carried out with CO1 (Parenrengi et al 2016), identification of flying fish morphology in the Makassar Strait found six species (Indrayani et al 2020), and the use of DNA analysis for identification of flying fish is much better than using morphological analysis which often results in errors (Gordeeva and Shakhovskoi 2017). Since limited research has been done on the genetic diversity of flying fish in the waters of Southeast Sulawesi, the findings of this study are useful information.…”
Section: Introductionmentioning
confidence: 99%